The OVERVIEW OF YOUTH PREPAREDNESS IN FACING EARTHQUAKE DISASTERS AT PADUKUHAN SINDET, TRIMULYO, JETIS, BANTUL - Amestiasih, Tia; Rahil, Nazwar Hamdani; Anwar, Khairil (Jurnal Keperawatan Respati Yogyakarta, 2021)
Yogyakarta location is near the confluence of 2 world plates and on the path of an active volcano in the world. This condition makes Yogyakarta vulnerable to earthquakes, both tectonic and volcanic. Jetis is a district in Yogyakarta that was most affected during the 2006 earthquake disaster. Jetis District is still one of the districts with high risk of earthquakes in the 2016-2020 period. In disaster conditions, youth become the age group that capable of performing important tasks in disaster management. Seeing this condition, it is important to know how prepared the youth is in the face of an earthquake. The purpose of this study is to determine youth preparedness in facing earthquake disasters. This study uses a descriptive analytic method. The population in this study were 51 youths in Sindet, Trimulyo, Jetis, Bantul, and total sample 34 which were taken using simple random sampling technique. Data collection was carried out using a questionnaire. The results showed that there were still 8.8% of respondents with almost ready preparedness category. Most respondents have preparedness in the ready category, but considering that there are still respondents in the almost ready category, recommendations are still needed to improve preparedness. Keywords: Disaster; Earthquake; preparedness